2002
DOI: 10.1073/pnas.092140799
|View full text |Cite
|
Sign up to set email alerts
|

Aldosterone signaling pathway across the nuclear envelope

Abstract: We describe the route by which aldosterone-triggered macromolecules enter and exit the cell nucleus of Xenopus laevis oocyte. Oocytes were microinjected with 50 fmol aldosterone and then enucleated 2-30 min after injection. After isolation, nuclear envelope electrical resistance (NEER) was measured in the intact cell nuclei by using the nuclear hourglass technique. We observed three NEER stages: an early peak 2 min after injection, a sustained depression after 5-15 min, and a final late peak 20 min after injec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
41
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 56 publications
4
41
0
Order By: Relevance
“…Oocytes injection, isolation of the nuclei and preparation of nuclear envelopes Oocytes were collected as previously described (Schäfer et al, 2002). For the triamcinolone acetonide (TA) experiments, oocytes were injected with 50 nl solution containing TA (TA concentration in the injection fluid: 2ϫ10 -5 mol l -1 in water; TA stock solution dissolved in ethanol: 10 -2 mol l -1 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Oocytes injection, isolation of the nuclei and preparation of nuclear envelopes Oocytes were collected as previously described (Schäfer et al, 2002). For the triamcinolone acetonide (TA) experiments, oocytes were injected with 50 nl solution containing TA (TA concentration in the injection fluid: 2ϫ10 -5 mol l -1 in water; TA stock solution dissolved in ethanol: 10 -2 mol l -1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Oberleithner et al (Oberleithner et al, 1994) showed in kidney cells that the NE responds to aldosterone by increasing both, NPCs density and NE permeability within 6 hours of hormone exposure. Using a nano-imaging technique, atomic force microscopy (AFM) (Binnig and Quate, 1986), we could visualize some of the endogeneous macromolecules on their route through the NPCs following aldosterone injection into X. laevis oocyte (Schäfer et al, 2002). Changes in NPC conformation were paralleled by sharp changes in NE electrical conductivity (Danker et al, 1999).…”
mentioning
confidence: 99%
“…Third, MR antagonists such as spironolactone or canrenone usually do not block rapid aldosterone effects, which indicates that these effects are not mediated by the MR but by an unrelated receptor. However, a few cases of rapid MR antagonist-sensitive aldosterone effects have been reported (13,18). These findings may suggest that at least some rapid effects are mediated via the classical intracellular MR.…”
Section: The Putative Aldosterone Membrane Receptormentioning
confidence: 99%
“…Then vasoconstrictor actions of Aldo were examined as in protocol 1. It has been demonstrated that this concentration of actinomycin D or cycloheximide prevents Aldoinduced genomic nuclear signaling (16) or de novo protein synthesis in rat aorta (17), respectively. We used same vehicle for actinomycin D or cycloheximide with that for spironolactone.…”
Section: Effect Of Actinomycin D or Cycloheximide On Aldoinduced Consmentioning
confidence: 99%